2018
DOI: 10.1021/acs.nanolett.8b02688
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Beam Epitaxy of Two-Dimensional In2Se3 and Its Giant Electroresistance Switching in Ferroresistive Memory Junction

Abstract: Ferroelectric thin film has attracted great interest for nonvolatile memory applications and can be used in either ferroelectric Schottky diodes or ferroelectric tunneling junctions due to its promise of fast switching speed, high on-to-off ratio, and nondestructive readout. Two-dimensional α-phase indium selenide (InSe), which has a modest band gap and robust ferroelectric properties stabilized by dipole locking, is an excellent candidate for multidirectional piezoelectric and switchable photodiode applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
159
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(176 citation statements)
references
References 59 publications
7
159
0
Order By: Relevance
“…Although SnTe nanoplates grown by molecular beam epitaxy (MBE) is not scalable at the moment, we believe that as more 2D ferroelectrics are being discovered, 2D ferroelectrics that can grow with uniform crystalline orientations can be found soon. For example, it is already found that In 2 Se 3 has in-plane polarization and can be grown by both MBE and CVD (chemical vapor deposition) [27][28][29][30]. We hope our design can open up a new direction of ferroelectric non-volatile memories.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although SnTe nanoplates grown by molecular beam epitaxy (MBE) is not scalable at the moment, we believe that as more 2D ferroelectrics are being discovered, 2D ferroelectrics that can grow with uniform crystalline orientations can be found soon. For example, it is already found that In 2 Se 3 has in-plane polarization and can be grown by both MBE and CVD (chemical vapor deposition) [27][28][29][30]. We hope our design can open up a new direction of ferroelectric non-volatile memories.…”
Section: Discussionmentioning
confidence: 92%
“…Although it is predicted that in-plane polarization survives in the 2D limit [19], currently it is hard to prepare free-standing 2D perovskite ferroelectrics. Surprisingly, the recent discovered in-plane polarization in 2D ferroelectrics is enhanced instead of reduced in thin films [25,[27][28][29][30]. For example in SnTe, compared with the bulk ferroelectric transition temperature of 98K, the one monolayer (ML) thin film has a critical temperature of 270K, and thicker films with 3 ML show robust spontaneous polarization even at room temperature [25,26].…”
Section: In-plane Polarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For 2D thin-film, a typical preparation method is a mechanical exfoliation, which was first used to prepare single-layer graphene in 2004 [18]. Since then, CVD [55], PLD [56], MBE [57], and pick-and-lift vdW techniques [58] were also used for preparing high-quality 2D thin films. Mechanical exfoliation is the main methodology to prepare the single-layer graphene.…”
Section: Preparation Of Thin-film Materialsmentioning
confidence: 99%
“…Their potential applications in different fields have been demonstrated. The first class of 2D pS is group III 2 ‐VI 3 ferroelectrics (M 2 X 3 , M = Al, Ga, In; X = S, Se, Te),7,8 and some of them have been synthesized in experiment 4,9–13. Particularly, ferroelectric In 2 Se 3 had been applied to data storage with the switchable polarization, spintronics,9 and visible light absorption 10,14–17.…”
Section: Introductionmentioning
confidence: 99%